Learning engagement and psychological flexibility among Chinese adolescents: a moderated mediation model - Yue, Pengfei; Zhang, Jiaxin (Frontiers in Psychology, 2025)
BackgroundPsychological flexibility is a key factor in maintaining mental wellbeing. While previous studies have used professional Acceptance and Commitment Therapy (ACT) interventions to enhance psychological flexibility, our study proposes a new approach to enhance psychological flexibility based on the Development-in-Sociocultural-Context Model for Childrenl Acceptance and CommitmenMethodsThis study, adopting a positivist research approach, utilized a cross-sectional design. Data were collected from 750 students at three middle schools in Henan Province, China, through cluster random sampling. This approach yielded 750 questionnaires. The participants sequentially completed three questionnaires: the Utrecht Work Engagement Scale-Student (UWES-S), the Harsh Parenting Questionnaire, and the Avoidance and Fusion Questionnaire for Youth. After removing 45 invalid questionnaires due to incomplete responses and patterned answers, a total of 705 valid questionnaires were obtained, with 52.9% girls and an average age of 13.11 years (SD = 1.04), leading to an effectiveness rate of 94.00%. Upon data collection, SPSS 26.0 software was used for correlation analysis, mediation analysis, and moderated mediation analysis to assess the relationships between variables.Results(1) Learning engagement positively predicts psychological flexibility; (2) harsh parenting mediates the relationship between learning engagement and psychological flexibility; and (3) gender moderates the impact of harsh parenting on psychological flexibility, with a more significant negative effect on females than males.ConclusionThis study highlights a novel approach for enhancing psychological flexibility among Chinese adolescents, demonstrating that by increasing their learning engagement, adolescents can effectively improve their psychological flexibility. Future research could investigate various cultural, age, and occupational groups to explore effective approaches for enhancing psychological flexibility in diverse populations, which is vital for promoting human mental wellbeing.